2011
DOI: 10.1182/blood-2011-01-326827
|View full text |Cite
|
Sign up to set email alerts
|

SuperSAGE evidence for CD14++CD16+ monocytes as a third monocyte subset

Abstract: Monocytes are a heterogeneous cell population with subset-specific functions and phenotypes. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
527
3
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 473 publications
(568 citation statements)
references
References 41 publications
(70 reference statements)
33
527
3
5
Order By: Relevance
“…11,12 Highest TNFa expression was found in non-classical monocytes, consistent with a strong pro-inflammatory potential. HLA-DR and CCR5 were both expressed at highest levels in the intermediate subset, indicating a pronounced role in antigen-presentation as well as chemotactic response to tumor signals, respectively.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…11,12 Highest TNFa expression was found in non-classical monocytes, consistent with a strong pro-inflammatory potential. HLA-DR and CCR5 were both expressed at highest levels in the intermediate subset, indicating a pronounced role in antigen-presentation as well as chemotactic response to tumor signals, respectively.…”
Section: Discussionmentioning
confidence: 67%
“…While the low and uniform levels of VEGF transcripts were unexpected, all other results were in line with previously published reports on gene expression patterns of monocyte subsets. 11,12 Importantly, there were no significant differences in the gene expression profiles between monocyte subsets isolated from healthy controls and mCRC patients, even though we have previously shown that the frequency of subpopulations differs significantly between healthy individuals and mCRC patients. 16 Furthermore, chemotherapy did not alter the gene expression profile of monocyte subsets in mCRC patients.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations